Implementasi Fungsi Imarah melalui Program Pengajian Rutin di Masjid Jamik Silang Rukoh-Blangkrueng - Suhnul Abda; Vera Nurriza; Dini Afriani; Khairul Habibi (ANWARUL, 2026)
Mosques serve a strategic function in the lives of Muslims, not only as places for performing mahdhah worship but also as centers of education, Islamic propagation, and community development. One aspect of mosque management that determines the extent of its prosperity is imarah, namely efforts to enliven the role of the mosque through various religious and community activities. This study aimed to describe the implementation of the imarah function through a regular Islamic study program at Masjid Jamik Silang Rukoh–Blangkrueng and to identify the factors supporting and hindering its implementation. The study employed a qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation involving mosque administrators and congregants. The results showed that the regular Islamic studies conducted every Tuesday, Friday, and Saturday evening through the methods of Islamic text study, lectures, and discussions constituted a tangible implementation of the imarah function. The program enhanced the congregants’ religious understanding in the fields of Islamic jurisprudence, morality, Qur’anic exegesis, and Sufism, while also strengthening Islamic brotherhood and fostering the community’s sense of ownership of the mosque. The success of the program was supported by schedule consistency, the competence of the speakers, and the active participation of congregants, whereas the obstacles included congregants’ limited time, weather conditions, and the lack of participant regeneration among the younger generation. This study concludes that the continuity of the regular Islamic study program is an important indicator of the successful implementation of the imarah function in fostering a prosperous community-based mosque. These findings provide practical implications for mosque administrators to maintain program consistency, increase the participation of the younger generation, and strengthen the sustainable management of religious activities.